Associations between motor competence and executive functions in children and adolescents: a systematic review and meta-analysis - Bao, R.; Wade, L.; Leahy, A. A.; Owen, K. B.; Hillman, C. H.; Jaakkola, T.; Lubans, D. R. (Sports Medicine, 2024)
Background: Motor competence and executive functions co-develop throughout childhood and adolescence, and there is emerging evidence that improvements in motor competence may have cognitive benefits in these populations. There is a need to provide a quantitative synthesis of the cross-sectional, longitudinal and experimental studies that have examined the association between motor competence and executive functions in school-aged youth. Objectives: The primary aim of our systematic review was to synthesise evidence of the association between motor competence and executive functions in school-aged children and adolescents (5-18 years). Our secondary aim was to examine key moderators of this association. Methods: We searched the PubMed, PsycINFO, Scopus, Ovid MEDLINE, SPORTDiscus and EMBASE databases from inception up to 27 June 2023. We included cross-sectional, longitudinal and experimental studies that assessed the association between motor competence (e.g., general motor competence, locomotor skills, object control skills and stability skills) and executive functions (e.g., general executive functions, inhibition, working memory and cognitive flexibility) in children and adolescents aged 5-18 years. Results: In total, 12,117 records were screened for eligibility, and 44 studies were included. From the 44 included studies, we meta-analysed 37 studies with 251 effect sizes using a structural equation modelling approach in the statistical program R. We found a small positive association (r = 0.18, [95% confidence interval (CI) 0.13-0.22]) between motor competence and executive functions. The positive associations were observed in cross-sectional (r = 0.17, [95% CI 0.13-0.22]), longitudinal (r = 0.15, [95% CI 0.03-0.28]) and experimental studies (r = 0.25, [95% CI 0.01-0.45]). We also found that general motor competence (r = 0.25, [95% CI 0.18-0.33]), locomotor (r = 0.15, [95% CI 0.09-0.21]), object control (r = 0.14, [95% CI 0.08-0.20]) and stability (r = 0.14, [95% CI 0.08-0.20]) skills were associated with executive functions. We did not find any moderating effects for participants` age on the associations between motor competence and executive functions. Conclusions: Our findings suggest a small-to-moderate positive association between motor competence and executive functions in children and adolescents. The small number of experimental studies included in this review support the assertion that interventions targeting children`s motor competence may be a promising strategy to improve their executive functions; however, more research is needed to confirm these findings. Future studies should explore the underlying mechanisms linking motor competence and executive functions as their comprehension may be used to optimise future intervention design and delivery.